Assesing Sino-Russian strategic synergies in North Africa (Journal of the Spanish Institute for Strategic Studies, 2025)
This paper examines the synergistic effects of increased collaboration between Russia and the PRC in North Africa. It argues that their coordinated efforts across diplomatic, information, military, and economic domains could significantly undermine Western regional interests. While scholars have analyzed the individual challenges posed by Russia and China, little attention has been given to how their combined actions might amplify their impact. Employing the strategic analysis model from the Army War College's Carlisle Scholar Program, the research identifies key areas of alignment in their regional approaches, including coordinating positions in multilateral forums, amplifying narratives through state media, launching joint naval exercises, and connecting overland and maritime economic corridors. Despite their distinct priorities and capabilities, the analysis finds that North Africa presents unique opportunities for Russia and China to advance their shared goals of expanding global influence and eroding the Western-led international order. To effectively counter this challenge, the paper argues that the United States and Europe must craft proactive, principled engagement strategies underpinned by robust partnerships with North African nations. These strategies should provide viable alternatives to exploitative Chinese and Russian economic arrangements, address the root causes of instability through governance and security assistance, and leverage coordinated diplomacy and sanctions policies for a unified Western approach. The paper underscores the importance of continued research on the evolution of Sino-Russian collaboration to inform adaptive policy responses in an era of intensifying strategic competition